Acupuncture for the Treatment of Alzheimer's Disease: An Overview of Systematic Reviews - Huang, Jinke; Shen, Min; Qin, Xiaohui; Wu, Manli; Liang, Simin; Huang, Yong (Frontiers in Aging Neuroscience, 2020)
Background: Acupuncture may be an effective approach to treat Alzheimer’s disease (AD), the purpose of this overview was to summarize the evidence from systematic reviews (SRs)/meta-analysis (MAs) on acupuncture for AD. Methods: We searched the literature using 8 databases from their inception to Feb 2020. The methodological quality, reporting quality, risk of bias of included SRs, and evidence quality of outcome measures were assessed, respectively, by the Assessing the Methodological Quality of Systematic Reviews 2 (AMSTAR-2), the Risk of Bias in Systematic reviews (ROBIS) tool, the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), and Grades of Recommendations, Assessment, Development and Evaluation (GRADE). Results: Ten SRs/MAs met all inclusion criteria. According to the evaluation results of AMSTAR-2, all SRs/MAs were rated critically low quality. With the PRISMA, the reporting was relatively complete, but there were still some reporting flaws in the topic of protocol and registration, search strategy, risk of bias, additional analyses and funding. Based on ROBIS tool, only 2 SRs/MAs (20%) were low risk of bias. With GRADE system, no high-quality of evidence was found, only 4 outcomes provided moderate-quality evidence. Among the downgraded factors, risk of bias within the original trials was the most common, followed by inconsistency, imprecision, and publication bias. Conclusions: Acupuncture may be beneficial for AD. However, due to the low quality of SRs/MAs supporting these results, high-quality studies are required to provide robust evidence for definitive conclusions.